Refleksi Filosofis atas Kajian Teori dan Praktik Akuntansi Syariah: indonesia - Sunarno, Reyhan Dzikriansyah (Owner : Riset dan Jurnal Akuntansi, 2024)
This study examines philosophical reflections on Sharia accounting theory and practice through the lenses of ontology, epistemology and axiology. Sharia accounting, rooted in Islamic principles, emphasizes accountability, fairness, and honesty as fundamental principles. Ontologically, Sharia accounting is conceptualized within the framework of Islamic law and muamalat (transactions), ensuring compliance with Sharia principles in financial reporting. Epistemologically, Sharia accounting involves the acquisition of knowledge through Islamic jurisprudence (fiqh) and empirical observation, ensuring accuracy and compliance with Sharia values. Axiologically, Sharia accounting aims to achieve economic fairness, justice and ethical integrity, aligning financial practices with moral principles originating from Islamic teachings. This study contributes to a deeper understanding of how Sharia accounting integrates Islamic values into its theoretical framework and operational practices, ensuring alignment with worldly and spiritual goals